Expression of Orai1 and STIM1 in human oral squamous cell carcinogenesis - Yen-Yun Wang; Wen-Chen Wang; Chiang-Wei Su; Ching-Wei Hsu; Shyng-Shiou Yuan; Yuk-Kwan Chen (Elsevier, 2022)
Background/purpose: Return of Ca2+ to endoplasmic reticulum is mediated by Orai/STIM-mediated store-operated Ca2+ entry (SOCE) channel. We aimed to investigate Orai1 and STIM1 expressions in human oral carcinogenesis. Materials and methods: Sixty-six oral squamous cell carcinomas (OSCCs), 14 oral potentially malignant disorders (OPMD) with moderate-severe oral epithelial dysplasia (OED), 19 OPMD with mild OED, and 14 normal oral mucosa (NOM) samples were subjected to immunohistochemical staining. Two human oral cancer cell lines (OCCLs), an oral premalignant cell line (DOK), and a normal oral keratinocyte culture (HOK) were used for Western blot and real-time quantitative reverse transcription-polymerase chain reaction. OCCLs were evaluated for proliferation, migration, and invasion assays. Results: Orai1 and STIM1 protein and mRNA expressions in OSCC were significantly enhanced as compared with normal samples. Protein expressions of Orai1 and STIM1 in OCCLs were significantly enhanced as compared with HOK. Significant decreases in degrees of proliferation, migration and invasion were noted in OCCLs with Orai1 and STIM1 siRNA transfection as compared with those without transfection. Significantly increased Orai1 and STIM1 protein levels were noted in OPMD with moderate-severe OED as compared with those with mild OED. Conclusion: Our results indicate that Orai1 and STIM1 overexpression is associated with human oral carcinogenesis.